2021
DOI: 10.1371/journal.pone.0245180
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbiome structure and its network profiles to four soil amendments in monocropping strawberry greenhouse

Abstract: With the constant surge of strawberry cultivation and human demand, widespread concern has been expressed about the severe soil and plant health problems caused by continuous strawberry cropping, particularly monocropping in greenhouses. Effective microorganisms (EM) and Bacillus subtilis (BS) have been extensively commercialized as biological control agents (BCAs) to promote plant growth and yield enhancement. However, their effects on soil microbes are obscure. To regulate the microbial community in continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Utilizing network analysis, the co-occurrence patterns of bacterial taxa were illustrated with the R package igraph [ 37 , 38 ]. We adopted Spearman’s correlation test to obtain a strong correlation ( r > |0.9|, p < 0.01) between the 30 most abundant genera of bacterial communities.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing network analysis, the co-occurrence patterns of bacterial taxa were illustrated with the R package igraph [ 37 , 38 ]. We adopted Spearman’s correlation test to obtain a strong correlation ( r > |0.9|, p < 0.01) between the 30 most abundant genera of bacterial communities.…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms are essential for maintaining soil fertility and ecological function (Alami et al, 2021; Corato, 2020; Shen et al, 2020). Studies have identified soil microbial communities as critical to CC sickness (Chen et al, 2022; Liu, Khan, et al, 2021; Liu, Wang, et al, 2021). Soil physicochemical properties also regulate microbial responses to nitrogen, phosphorus and potassium availability during CC (Tan et al, 2021; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurrence network analysis is a novel method that helps us to understand the complex association among microbial communities in soil ecosystems and highlights how such complex interaction is impacted by agricultural activities ( Goberna and Verdú, 2022 ). The more clustered network and firmly connected microbial community in cow dung could potentially make the community highly stable ( Sun et al., 2015 ) to soil sickness owing to continuous ginseng monocropping ( He et al., 2021 ), pathogen colonization ( Rybakova et al., 2017 ), and environmental stresses ( He et al., 2021 ), thereby maintaining soil health ( Liu et al., 2021a ). In contrast, scattered niches in control and canola would harm the prompt defense against foreign pathogen invasion ( Tao et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%